Underwater Acoustic Communication Quality Evaluation Model Based on USV - Zhichao Lv; Jie Zhang; Jiucai Jin; Qi Li; Lanjun Liu; Pengcheng Zhang; Baoru Gao (Shock and Vibration)
The unmanned surface vehicle (USV) integrated with acoustic modems has some advantages such as easy integration, rapid placement, and low cost, which becomes a kind of selective novel node in the underwater acoustic (UWA) communication network and a kind of underwater or overwater communication relay as well. However, it is difficult to ensure the communication quality among the nodes on the network due to the random underwater acoustic channel, the severe marine environment, and the complex mobile node system. Aiming to model the communication characteristics of the USV, the multipath effect and Doppler effect are main concerns for the UWA communication in this paper, so that the ray beam method is utilized, the channel transmission function and the channel gain are obtained, and the mobile communication quality evaluation model is built. The simulation and lake experiments verify that the built mobile UWA communication quality evaluation model on USV can provide preference and technique support for USV applications.